A Comparative Mössbauer Study of the Mineral Cores of Human H-Chain Ferritin Employing Dioxygen and Hydrogen Peroxide as Iron Oxidants - Bou-Abdallah, Fadi (2007)
Ferritins are ubiquitous iron storage and detoxification proteins distributed throughout the plant and animal kingdoms. Mammalian ferritins oxidize and accumulate iron as a ferrihydrite mineral within a shell-like protein cavity. Iron deposition utilizes both O(2) and H(2)O(2) as oxidants for Fe(2+) where oxidation can occur either at protein ferroxidase centers or directly on the surface of the growing mineral core. The present study was undertaken to determine whether the nature of the mineral core formed depends on the protein ferroxidase center versus mineral surface mechanism and on H(2)O(2) versus O(2) as the oxidant. The data reveal that similar cores are produced in all instances, suggesting that the structure of the core is thermodynamically, not kinetically controlled. Cores averaging 500 Fe/protein shell and diameter ∼ 2.6 nm were prepared and exhibited superparamagnetic blocking temperatures of 19 and 22 K for the H(2)O(2) and O(2) oxidized samples, respectively. The observed blocking temperatures are consistent with the unexpectedly large effective anisotropy constant K(eff) = 312 kJ/m(3) recently reported for ferrihydrite nanoparticles formed in reverse micelles (Duarte et al., Nanotechnology 17 (2006) 5549-5555). All ferritin samples exhibited two magnetic phases present in nearly equal amounts and ascribed to iron spins at the surface and in the interior of the nanoparticle. At 4.2 K, the surface spins exhibit hyperfine fields, H(hf), of 436 and 445 kOe for the H(2)O(2) and O(2) samples, respectively. As expected, the spins in the interior of the core exhibit larger H(hf) values, i.e. 478 and 486 kOe, respectively. The slightly smaller hyperfine field distribution DH(hf) for both surface (78 kOe vs. 92 kOe) and interior spins (45 kOe vs. 54 kOe) of the O(2) sample compared to the H(2)O(2) samples implies that the former is somewhat more crystalline.